The effect of climate change on economic growth: Evidence from Sub-Saharan Africa - Paul Alagidede; George Adu; Prince Boakye Frimpong (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper is a contribution to the empirics of climate change and its effect on sustainable economic growth in Sub-Saharan Africa. Using data on two climate variables, temperature and precipitation, and employing panel cointegration techniques, we estimate the short- and long-run effects of climate change on growth. We establish that an increase in temperature significantly reduces economic performance in Sub-Saharan Africa. Furthermore, we show that the relationship between real gross domestic product per capita on one hand, and the climate factors on the other, is intrinsically non-linear.
Keywords: I18; 330; climate change; Sub-Saharan Africa; sustainable growth; panel cointegration